THE RELATION BETWEEN TEACHER’S SELF-DISCLOSURE AND STUDENT’S MOTIVATION TO LEARN - Zardeckaite-Matulaitiene, Kristina; Paluckaite, Ugne (European Scientific Journal, ESJ, 2013)
Teacher communication with students is an essential part of successful and inspiring teaching and learning process. Usually researches distinguish teacher immediacy and self-disclosure as the most influencing factors of teacher communication related to student’s motivation to learn. Most of the studies pay attention to immediacy created by the teacher in the class and its relation to students’ motivation. However, little is known about teacher’s disclosure influence on students’ motivation to learn. So, the aim of this literature review is to analyze the peculiarities of teacher’s self-disclosure and its relation to students’ motivation to learn. The literature review has shown that teacher’s self-disclosure may be an effective instrument for the teachers to motivate students to learn. The review has also shown that teacher’s self-disclosure should be relevant and appropriate in the current situation – teacher always has to make a decision: to disclose or not.